VARIASI TRACE GASES SELAMA 10 TAHUN DAN PENCAMPURAN DI SEKITAR LAPISAN TROPOPAUSE DI INDONESIA BERBASIS SATELIT (TRACE GASES VARIATION FOR 10 YEARS AND MIXING AROUND THE TROPOPAUSE LAYERS IN INDONESIA BASED ON SATELLITE) - Novita Ambarsari; Ninong Komala; Fanny Aditya Putri (Jurnal Sains Dirgantara, 2017)
Measurement of trace gases (CO, O3, CH3Cl, HCl, H2O, and HNO3) and temperatures around upper troposphere/lower stratosphere (UT/LS) or rather around Tropical Tropopause Layer (TTL) in Indonesia by using Microwave Limb Sounder (MLS) instrument board on Satellite AURA for 2005-2014 period to make variations of these gases over the 10 years around TTL allows to be studied more deeply. TTL becomes the main route entry of chemical compounds and aerosols originating in the troposphere into the stratosphere. The composition of minor gases in the TTL is very important because it affects the global radiation budget. Analysis of vertical profiles of these gases in the TTL was done to determine the suitability of the concept of TTL which starts from the upper troposphere to the lower stratosphere. Other method are the time series diagram of the altitude (height versus time series cross section) which shows the annual and interannual variations in vertical profiles of these gases in the TTL and the possible influence of the dynamics of the atmosphere. The results showed correlation of these gases with ozone showed most of the air in the stratosphere is experiencing mixing in the TTL. In addition, changes in concentration and temperature values in the TTL have been calculated using the trends of each parameter and it is known that the parameters of HCl, CH3Cl, and temperature show respective decreases of -0.036 ppmv, -0.024 ppmv, and -0.456 K. As for other parameters such as ozone, CO, H2O, and HNO3 showed an increase of respectively 0.0036 ppmv, 0.0096 ppmv, 0.108 ppmv, and 0.06 ppmv. AbstrakPengukuran trace gases (CO, O3, CH3Cl, HCl, H2O, HNO3) dan temperatur di sekitar lapisan troposfer atas/stratosfer bawah (UT/LS) atau tepatnya di sekitar Tropical Tropopause Layer (TTL) di Indonesia menggunakan instrumen Microwave Limb Sounder (MLS) pada Satelit AURA periode 2005-2014 menjadikan variasi gas-gas tersebut selama 10 tahun di sekitar TTL memungkinkan untuk dikaji lebih dalam. TTL menjadi jalur utama masuknya senyawa-senyawa kimia dan aerosol yang bersumber di troposfer ke stratosfer. Komposisi gas-gas minor di TTL sangat penting karena mempengaruhi budget radiasi global. Analisis profil vertikal gas-gas tersebut di TTL dilakukan untuk mengetahui kesesuaian konsep TTL yang dimulai dari lapisan troposfer atas hingga ke stratosfer bawah. Metode lainnya adalah dengan diagram time series terhadap ketinggian (time series versus height cross section) yang menunjukkan variasi tahunan maupun antar tahunan profil vertikal gas-gas tersebut di TTL serta kemungkinan adanya pengaruh dari proses dinamika atmosfer. Hasil penelitian menunjukkan korelasi gas-gas tersebut dengan ozon menunjukkan adanya sebagian udara di stratosfer yang mengalami pencampuran di wilayah TTL. Selain itu, perubahan nilai konsentrasi dan temperatur di TTL telah dihitung menggunakan trend masing-masing parameter dan diketahui bahwa parameter HCl, CH3Cl, dan temperatur menunjukkan penurunan masing-masing sebesar  -0,036 ppmv, -0,024 ppmv, dan -0,456 K. Adapun parameter lain seperti ozon, CO, H2O, dan HNO3 menunjukkan adanya peningkatan masing-masing sebesar 0,0036 ppmv, 0,0096 ppmv, 0,108 ppmv, dan 0,06 ppmv.